Determinants of Inflation in Mozambique - Ubide, Angel (IMF Working Papers; Working Paper ;, 1997)
Mozambique's inflation rate was consistently high until 1995, and then plunged in 1996 to 17 percent from 70 percent in 1994. This paper suggests that Mozambique's inflation pattern is a combination of a 'fundamental' trend set by economic policies, seasonal behavior that follows closely that of agriculture, and a collection of irregular events that corresponds mainly to agroclimatic conditions. The empirical results show that the marked tightening of monetary policy in 1996 was the ultimate reason for the control of inflation in 1996, and hence seems to correspond to a change in the 'fundamental' trend of inflation that may have long-lasting effects.